Penguatan profil pelajar pancasila menggunakan model value clarification technique (vct) tipe perisai kepribadian pada pendidikan pancasila sd negeri 03 pontianak timur - Miftah Amelia; Syarifah Asmiati; Maha Lastasa Buju Basafpipana Habaridota (Universitas Sebelas Maret, 2025)
This research is motivated by the VCT model has been applied in general outline has not used the various types in the model, so the researcher wants to focus on using the VCT model type of personality shield, especially the dimension of mutual cooperation in Pancasila Education deliberation material. The objectives of the study are divided into three, namely planning, implementation, and evaluation. To describe the strengthening of the Pancasila student profile. Descriptive research method with a qualitative approach, data collected observation, interviews and documentation, data sources of class IV B teachers, presented systematically contextually and factually. The results of the study concluded: 1) Planning to strengthen the Pancasila student profile, has been carried out by creating teaching modules, developing models, LKPD, profile values, especially the dimension of mutual cooperation. 2) Implementation of the steps of the VCT model type of personality shield, has been carried out providing a table of personality shields, and clarifying behavioral values that encourage profile values, especially the dimension of mutual cooperation in students. 3) Evaluation of the strengthening of the Pancasila student profile, has been carried out test techniques in the form of LKPD, and types of test evaluations to assess students' affective.